2012
DOI: 10.4049/jimmunol.1102002
|View full text |Cite
|
Sign up to set email alerts
|

Human NK Cells Induce Neutrophil Apoptosis via an NKp46- and Fas-Dependent Mechanism

Abstract: Polymorphonuclear neutrophils (PMN) are potent inflammatory effector cells essential to host defense, but at the same time they may cause significant tissue damage. Thus, timely induction of neutrophil apoptosis is crucial to avoid tissue damage and induce resolution of inflammation. NK cells have been reported to influence innate and adaptive immune responses by multiple mechanisms including cytotoxicity against other immune cells. In this study, we analyzed the effect of the interaction between NK cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 49 publications
6
86
0
Order By: Relevance
“…Thus, both normal and leukemic neutrophils, obtained from patients with chronic myeloid leukemia, can inactivate NK cells and trigger ROS-dependent parthanatic cell death in NK cells (28)(29)(30). By contrast, we have recently demonstrated that NK cells promote neutrophil apoptosis by Fas and NKp46-dependent mechanisms (8). Furthermore, recent interim reports from the European Stop Tyrosine Kinase Inhibitor Study and Stop Imatinib (STIM) trials, aiming at evaluating the possibility to stop tyrosine kinase inhibitor therapy in chronic myeloid leukemia, suggest that intact NK cell function is pivotal for a favorable outcome (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, both normal and leukemic neutrophils, obtained from patients with chronic myeloid leukemia, can inactivate NK cells and trigger ROS-dependent parthanatic cell death in NK cells (28)(29)(30). By contrast, we have recently demonstrated that NK cells promote neutrophil apoptosis by Fas and NKp46-dependent mechanisms (8). Furthermore, recent interim reports from the European Stop Tyrosine Kinase Inhibitor Study and Stop Imatinib (STIM) trials, aiming at evaluating the possibility to stop tyrosine kinase inhibitor therapy in chronic myeloid leukemia, suggest that intact NK cell function is pivotal for a favorable outcome (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…After sedimentation of erythrocytes, granulocytes and PBMCs were separated by density gradient centrifugation. Remaining erythrocytes were lysed in distilled water as described elsewhere (8). The purity of granulocytes was .97%, with ,1% contaminating monocytes.…”
Section: Isolation Of Human Leukocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…NK cells also induce neutrophil apoptosis via an NKp46-and Fas-dependent mechanism, 25 and this may be involved in the resolution of acute inflammation. In the present study, we demonstrated an unreported interaction between NK cells and neutrophils via a paracrine secretion of IL-10.…”
Section: Circulation Research February 14 2014mentioning
confidence: 99%
“…NK cells are involved in regulating the activation and apoptosis of inflammatory cells, such as neutrophils and eosinophils8910. Furthermore, NK cells play a role in the recognition and clearance of eosinophils in the airway of asthmatic mice11.…”
mentioning
confidence: 99%